2014
DOI: 10.1159/000368223
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic Responses of Endothelial Outgrowth Cells to Protein-Coated Surfaces

Abstract: There is significant clinical need for viable small-diameter vascular grafts. While there are many graft biomaterials in development, few have been clinically successful. Evaluation of grafts with a clinically relevant model is needed to drive development. This work examined extracellular matrix coatings on the thrombotic phenotype of endothelial outgrowth cells (EOCs). EOCs were tested on flat plates and tubular grafts. Flat plate studies examined collagen I, collagen IV, fibronectin and α-elastin coatings. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…ePTFE vascular grafts (W.L. Gore) were constructed as described previously to ensure a uniform transition between the graft and the silicone tubing [27] and used as a clinical, negative control. Similarly, the ePTFE grafts were coated with 1 mg ml −1 equine collagen type I (Chrono-log Corp.) for use as a positive control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ePTFE vascular grafts (W.L. Gore) were constructed as described previously to ensure a uniform transition between the graft and the silicone tubing [27] and used as a clinical, negative control. Similarly, the ePTFE grafts were coated with 1 mg ml −1 equine collagen type I (Chrono-log Corp.) for use as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic baboon femoral arteriovenous shunts were performed as described previously [27]. In brief, autologous platelets were labeled with 111-Indium prior to device testing and reinfused into the animal.…”
Section: Methodsmentioning
confidence: 99%
“…58 Intimal hyperplasia after vascular injury can also be reduced by activated Protein C. 62,63 Activated Protein C acts to inhibit inflammation-induced EC apoptosis and permeability, thereby maintaining functional EC regulation of underlying smooth muscle cells. 64 Similar to ECs, EOCs can activate Protein C. 46,65 To enhance Protein C activation, EOCs were engineered to overexpress thrombomodulin via adenoviral transfection. Although in vitro Protein C activation was increased, 47 thrombomodulin overexpression by EOCs seeded onto an ePTFE graft did not significantly reduce intimal hyperplasia or thrombus formation compared with non-transfected EOCs in a rat model.…”
Section: Inhibiting Intimal Hyperplasiamentioning
confidence: 99%
“…36 Studies of EOCs seeded onto ePTFE coated with either collagen I or fibronectin indicated that EOCs had a more robust adhesion and proliferation potential on either of these proteins than on aelastin or collagen IV. 65 With either collagen I or fibronectin coatings, EOCs formed a confluent monolayer and were able to remain adherent at supraphysiological shear stresses. 65 The mechanical properties, particularly the elasticity, of polyurethanes have stimulated investigation into their utility as vascular graft materials.…”
Section: Synthetic Scaffoldingmentioning
confidence: 99%
See 1 more Smart Citation